Preserving Prairie: Restoring Fort Riley’s Grant Ridge - Michael Stubbs; Bruce Waugh (Symphony in the Flint Hills, 2013)
Alexander Gardner’s 1867 photograph of Fort Riley shows the fort protected by a massive ridge to the south - a classic Flint Hills escarpment. Named in honor of General Ulysses S. Grant, Grant Ridge formed the southern boundary of the original 1853 Fort Riley Military Reservation. (An introduction to the site of the 2013 Symphony in the Flint Hills.)
Keywords: Fort Riley; Grand Ridge; prairie; Alexander Gardener; General Ulysses S. Grant; military; army; Geary County; Freedom Park; Lands Coalition Initiative; government; energy; environment; nature; native; Kansas; tallgrass